Increasing Students' Communication Skills and Independence Through Realistic Mathematics Learning Assisted by Google Classroom - supartik supartik; Laili Habibah Pasaribu (Universitas Jambi, 2021)
The purpose and problem formulation of this research is to find out whether realistic mathematics learning assisted by google classroom can improve students' communication skills and independence. This research method is descriptive quantitative research. This research was conducted at SMP Negeri 1 Pangkat in February-March 2021 in the even semester of the 2020/2021 learning year. The sample in this study were 25 students who were taken from the total population of data and could represent the entire population with the sample collection technique, namely the random sampling technique. The instruments used were tests and questionnaires with the data analysis technique using multiple regression tests. The results of this study were tested with multiple correlation test which resulted in a significant value of 0.011 < 0.05 and F counting 5.663 > F table 3.42. With an increase in communication skills and student independence simultaneously (simultaneously) to variable Y is 34%. So it can be concluded that there is an increase in students' communication skills and independence through realistic mathematics learning (PMR) assisted by google classroom.